A inclusão de alunos com transtorno do espectro autista (TEA) na educação infantil: formação de professores, políticas públicas e práticas pedagógicas - Soares, Rosângela Teles Carminati (2022)
Early Childhood Education is the first stage of Basic Education, therefore inclusion in this period is essential for the child to integrate into the school environment and fulfill its purpose of developing in an integral way in the physical, psychological and social aspects. In this context, teacher training is extremely important. It is understood that it is necessary to give voice to the subjects who are involved in the inclusion process. Thus, this research aims to present, in the teacher’s view, the perception of these early childhood education professionals with regard to their initial and continuing education for the school inclusion of students with Autism Spectrum Disorder (ASD). In particular, Paulo Freire's writings are used for discussions on teacher education and Lev Semenovich Vygotsky as the basis of the teaching learning process. The research was qualitative, descriptive and exploratory, through content analysis. Twenty teachers who worked with students with ASD participated in the research, in 2019, from five different teaching institutions of the municipal Early Childhood Education network border region. To reach this our goal, the technique of individual, semi-structured interview was used, with fifteen guiding questions. We have concluded that teacher training is essential for the inclusive pedagogical practices of teachers, as the child learns and develops from the quality of the mediations the child receives, although other factors need to be taken into account, such as the preparation of the school environment, necessary support and resources for teachers and students, among others. However, in order to achieve this objective, public sector investment with public policies aimed at education for all is necessary.